La sociedad civil en la Polonia de los primeros años ochenta como factor de descomposición del régimen comunista - Ricardo Martín de la Guardia; José Luis Orella (Amnis)
The 1980s saw the gradual dissolution of the power system in Poland. Civil society seemed to emerge from its lethargy stimulated by a situation resulting from the impossibility of overcoming the economic crisis. While the standard of living of Poles had deteriorated due to the institutional and economic deadlock in Poland in the mid-1980s, the only solution for many was to support an opposition movement that was finally channelled through Solidarity, a trade union that from the beginning of the decade - in contrast to the other Eastern countries - had achieved great notoriety and enormous social support. Thus, at the beginning of the transition to democracy, the strength of a society with widely dispersed interests, but which Solidarity was able to unite at the most difficult moment, when it had to openly confront the state, was to play a key role.